Analisis kualitas produk, label halal, dan harga terhadap keputusan pembelian Tempe: Peran mediasi kepercayaan konsumen - Jamal, Afif Iqbal; Waluyo, Agus (Nur Science Institute, 2022)
This study aims to determine the effect of product quality, halal label, and price on tempe purchasing decisions, with trust as an intervening variable. Researchers used quantitative methods with data processing by filling out questionnaires given to Rumah Kedelai Grobogan consumers, especially the Grobogan community. The total respondents were 100 people using the prospective random sampling technique. The study conducted instrument testing, classical assumption tests, statistical tests, and path analysis. Results show that product quality and the halal label did not influence purchasing decisions for Tempe products at the Grobogan Soybean House. However, price had a significant positive effect on purchasing decisions. Product quality and the halal label did not affect trust, while price had a positive effect. Trust influenced purchasing decisions but did not mediate the relationship between product quality, the halal label, and price. These findings suggest that factors beyond product quality and halal labeling influence purchasing decisions and trust in Tempe products.